The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00217-020-03624-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of polyphenols, antioxidant capacity and minerals for the valorisation of ancient apple cultivars from Northeast Italy

Abstract: Nutritional properties and quality of apple fruits can be related to presence of secondary metabolite contents such as phytochemicals and mineral elements. In this paper, eight polyphenols, four major minerals (Na, K, Mg, Ca), total phenolic content and antioxidant capacity were determined in fourteen ancient apple cultivars grown in Friuli Venezia Giulia (Northeast Italy) to highlight their nutraceutical properties. Both apple peel and pulp were examined separately and results were compared to those of six wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 36 publications
8
40
0
Order By: Relevance
“…The concentration of quercetin found in the apples ranged between 1.10–11.61 mg/100 g DW with higher amounts for Beliy Naliv and Spartan cultivars and lowest amounts for Renet Simerenco and Richard cultivars. Rutin was a minor component among the other flavonoids, with highest concentration for Beliy Naliv, Montuan and Cretesc cultivars, being consistent with the literature [ 27 , 29 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The concentration of quercetin found in the apples ranged between 1.10–11.61 mg/100 g DW with higher amounts for Beliy Naliv and Spartan cultivars and lowest amounts for Renet Simerenco and Richard cultivars. Rutin was a minor component among the other flavonoids, with highest concentration for Beliy Naliv, Montuan and Cretesc cultivars, being consistent with the literature [ 27 , 29 ].…”
Section: Resultssupporting
confidence: 91%
“…The amounts of (-)-epicatechin determined in 14 ancient apple cultivars from Friuli Venezia Giulia (Italy) and six commercial apple cultivars varied from 9.10 to 85.39 mg/100 g of peel (FW) and from 7.12 to 27.06 mg/100 g of pulp (FW), while (+)-catechin varied from 3.53 to 20.20 mg/100 g in peel (FW) and from 4.21 to 16.51 mg/100 g of pulp (FW) [ 27 ]. Bondonno et al reported 10.93 mg (-)-epicatechin/100 g DW (whole apple) for the Golden Delicious apple cultivar harvested in Western Australian in 2015 season [ 28 ], while Preti et al reported for Golden Delicious the following values: 31.00 mg (-)-epicatechin/100 g and 10.27 mg (+)-catechin/100 g of apple peel (FW) and respectively, 7.49 mg (-)-epicatechin/100 g and 4.21 mg/100 g of apple pulp (FW) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Preti and Tarola [ 40 ] recently evaluated fourteen ancient apple cultivars grown in northeast Italy to investigate their nutraceutical properties comprising polyphenols, antioxidant capacity, as well as four major minerals (Na, K, Mg, Ca) in comparison to commercial cultivars. All the analyses were performed on apple peel and pulp, separately.…”
Section: Apple As a Functional Foodmentioning
confidence: 99%
“…The composition of fruits in terms of specialized metabolites depends on both genetic and environmental factors, although the former generally has a stronger effect. There are up to 3000 apple varieties and 2000 pear varieties worldwide, but only a few of these are cultivated commercially, restricting the choice for consumers [ 4 , 35 ]. The continual strong selection pressure imposed to breed elite cultivars with visually attractive and delicious fruits that withstand long storage periods [ 36 , 37 ] has reduced the content of bioactive compounds, including polyphenols [ 22 , 23 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in broad agreement ( Supplementary Table S1 ). Another study reported the chlorogenic acid content of Royal Gala, Golden Delicious and Fuji apple skins as ~12, ~6 and ~16 mg/100 g fw, and the same varieties accumulated ~1.4, ~0.8 and ~1.62 mg/100 g fw of phloridzin [ 35 ]. Compared to these regular cultivars, the analysis of nine ancient apple varieties revealed that the chlorogenic acid content was three times higher (~28 mg/100 g fw) in variety Dal Doc, and that the phloridizin content ranged from twice as high (~3 mg/100 g fw in variety Limoncei) to 10-fold higher (~14 mg/100 g fw in variety Di Corone) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%